Analisis Kinerja Keuangan Kabupaten/Kota Pemekaran di Sumatera Utara - Paidi Hidayat; Wahyu Ario Pratomo; D. Agus Harjito (Universitas Islam Indonesia, 2007)
This research attempts to analyze the implementation of regional autonomy to the financial performance in newly-formed district government of North Sumatra. It focuses on the performance of original regional income after fiscal decentralization and the regional financial independency. The result shows that regional autonomy has a positive impact on the growth of original regional income. However, the share of those incomes to regional budget is still small. The newly-formed districts in North Sumatra are unready to face the regional autonomy policy. Most of the newly-formed regencies/municipalities are very dependent to balanced fund through General Allocation Fund and Special Allocation Fund.Keywords: regional autonomy, original regional income, fiscal decentralization.